ANALISIS OPTIMALISASI HARGA SAHAM DI BURSA EFEK INDONESIA DENGAN PENDEKATAN, PRICE EARNING RATIO, INVESTASI AKTIVA TETAP DAN RETURN ON INVESTMENT BERBASIS TOTAL ASSET TURNOVER - Hermawati, Adya (Arthavidya Jurnal Ilmiah Ekonomi, 2013)
This research is to investigate the effect of Return on Investment (ROI), Price earning Ratio (PER), Total Asset Turnover (TAT) and Investment in Investment inInvestment inInvestment inInvestment inInvestment inInvestment in Investment inInvestment inInvestment in Fixed ixed ixed ixed ixed assets assetsassetsassetsassets to the level of stock price at the propertypropertyproperty propertypropertyproperty company, and to investigate the dominant variable that affects the stock price significantly. The method used in this reseacrh is purposive sampling with the criteria as below; a. The companies are listed in Indonesian Stock Exchange at least for three years from 2005 until 2009; b. The financial statement has been published from 2005 to 2009; c. The company has data of financial ratios; d. The company as positive earnings during the period research.Kata kunci: ROI, PER, TAT, Investment in Investment inInvestment inInvestment inInvestment inInvestment inInvestment in Investment in Investment in Fixed assetsixed assetsixed assetsixed assets ixed assetsixed assetsixed assetsixed assets, Stock Price